Comparative focusing properties of spherical and plane microwave zone plate antennas - Dey K.K.; Khastgir P. (My University, 2025)
An analysis is made of the lens-like property of plane and spherical zone plate antennas, and source distance-image distance relations are derived. Expressions for the focal lengths are also obtained. The source-distance discriminating property of the spherical zone plate antenna is studied and computations for the axial variation of intensity for the plane and the spherical zone plate antennas are mode for various situations. © 1973 Taylor and Francis Ltd.